Placemaking in a translocal receiving community: The relevance of place to identity and agency. (January 2015) - Main, Kelly; Sandoval, Gerardo Francisco
Recent case studies of receiving communities have established that translocal immigrants are transforming their neighbourhoods, producing spaces of identity. While these studies have focused on the reshaping of local power dynamics, less attention has been given to the spaces, themselves, and the qualities that influence identity. This study utilises place identity literature, from environmental psychology, to explore the remaking of MacArthur Park, a public space at the centre of a Mexican and Central American immigrant community in Los Angeles, California. We find that new 'place identities' are influenced by the specific physical, social, and cultural elements of the park, as study participants attempt to maintain identities influenced by important places in their sending communities. The result is a park that has emotional significance for participants, significance that leads to agency – everyday and political practices – to protect the park, sometimes in the face of immense challenges.